The Influence of Leadership Style Mediated by Intellectual Capital and Innovation on International Manufacturing Company Performance - Wisnu Yuwono; Davin Ewaldo; Dewi Khornida Marheni; Suyono Saputra (Dinasti International Journal of Education Management And Social Science, 2025)
Currently, companies face uncertain situations due to the effects of unstable world geopolitical conditions, and the role of company leaders will affect innovation and company performance. This study analyzes the relationship between leadership style, intellectual capital, and innovation on employee performance in foreign manufacturing companies in Batam City, Indonesia. This study uses quantitative methods with data collection through questionnaires distributed to employees in foreign manufacturing companies in Batam City totaling 303 respondents. The results showed that transformational and authentic leadership styles had a significant positive influence on employee innovation and performance, while transactional leadership style showed a stronger influence in a stable business environment. Intellectual capital proved to be an important mediator in the relationship between leadership style and innovation, which in turn has an impact on improving company performance. This study provides practical implications for managers of manufacturing companies to adopt a leadership style that suits the dynamics of the work environment and maximize intellectual capital to encourage innovation and optimal employee performance.